Pengaruh Kualitas Pelayanan, Harga Dan Kepercayaan Terhadap Loyalitas Pelanggan Melalui Kepuasan Pelanggan - Imelda Aprileny; Afzalur Rochim; Jayanti Apri Emarawati (Jurnal Ekonomi, 2022)
This study aims to determine how much influence service quality, price and trust have on customer loyalty through customer satisfaction at Al Azhar 4 Islamic High School students.This study uses an associative research strategy which is measured by using the path analysis method with SPSS 22.00. The population of this study were students of SMA Islam Al Azhar 4 Kemang Pratama, Bekasi, with a total of 100 respondents. The data used in this study are primary data. Data collection techniques used two methods, namely library research and field studies by distributing questionnaires. The research results prove that 1). Service quality has a direct effect on customer satisfaction. 2). Price has no direct effect on customer satisfaction. 3). Trust has no direct effect on customer satisfaction. 4). Service quality has a direct effect on customer loyalty. 5). Prices have a direct effect on customer loyalty. 6). Trust has a direct effect on customer loyalty. 7). Customer satisfaction has no direct effect on customer loyalty. 8). The indirect effect of service quality on customer loyalty through customer satisfaction is not significant. 9). The indirect effect of price on customer loyalty through customer satisfaction is not significant. 10). The indirect effect of trust on customer loyalty through customer satisfaction is not significant.